PENGEMBANGAN PERANGKAT LUNAK UNTUK PENERAPAN TEKNIK PINCH DENGAN MELIBATKAN KENDALA RUGI TEKANAN - Willy Adriansyah; Aryadi Suwono (Mesin, 1996)
The existing software of pinch technique provide only the tool for the heat exchanger network design. To improve the reliability of the software, in particularly for retroï¬tting the existing system, several additional aspects need to be included. In this paper, an algorithm to determine the optimum condition of heat exchangers for a specified allowable head loss is proposed. With this new method, the retroï¬t design of an existing system can be done even by taking into consideration of using the existing ï¬‚uid circulation systems (i.e. pumps and compressors). The proposed method of heat exchanger can also be used under the pressure drop constraints on both tube and shell sides.